Smart City Concept - Umida Uzakova Ruziyevna (Genius Publishing Group, 2022)
A smart city is largely composed of Information and Communication Technologies (ICT), which is the basis for developing, deploying and stimulating sustainable development practices to solve growing urbanization problems.
Keywords: Wireless technology; power; monetization; infrastructure